ACTIVE STUDENTS PERCEPTIONS ON COLD CALLING STRATEGY (CCS) IN ELT CONTEXT - Putri, Annisa Amelia; Abdul, Nurdevi Bte; Azis, Awalia (FKIP Unismuh Makassar, 2025)
This research aimed at finding out the active students’ perceptions of CCS in classroom discussion. The method of this research was basic qualitative study (descriptive qualitative). Data of the research were collected through observation in order to select the research subject and interview. This research was conducted at SMA Negeri 8 Makassar which running in the eleventh grade with a total of 10 research subjects. The techniques of data analysis were data reduction, data display, and conclusion drawing/verification. The findings of this research showed that active students gave various opinions and perceptions. Majorities of them perceived a positive thoughts about CCS, where cold calling results in better levels of students comfort. In addition, the active students perceived that CCS are helpful to facilitating them to discuss their thoughts in front of the class, strengthening their comprehension of the material, and contributes positive impact on improves the academic performances. However, there were also some negative thoughts about CCS; feeling of anxiousness, embarrassed by cold calling, disappointment of not receiving cold call by the teacher while they wanted to contribute their opinion in a discussion. In short, despite of some inconvenient feelings they were experienced, active students were agree if CCS use more frequently in the English language learning; especially in terms of classroom discussion.